State-of-the-art catechol porphyrin COF catalyst for chemical fixation of carbon dioxide via cyclic carbonates and oxazolidinones - Saptal, Vitthal; Shinde, Digambar Balaji; Banerjee, Rahul; Bhanage, Bhalchandra M. (Catalysis Science & Technology, 2016)
A highly porous, crystalline catechol porphyrin COF was synthesized and applied as an organocatalyst for the chemical fixation of carbon dioxide to synthesize value-added chemicals such as cyclic carbonates and oxazolidinones under solvent-free and transition-metal-free conditions. The high surface area and the functionalities of the COF catalyst act synergistically to activate the starting material. The 2,3-DhaTph shows excellent activity towards cyclic carbonates at the atmospheric pressure of carbon dioxide. Additionally, this catalytic system is recyclable in nature and provides a higher turnover number than previously reported organocatalysts.

Room-temperature asymmetric transfer hydrogenation of biomass-derived levulinic acid to optically pure gamma-valerolactone using a ruthenium catalyst - Shende, Vaishali S.; Raut, Amol B.; Raghav, Prathamesh; Kelkar, Ashutosh A.; Bhanage, Bhalchandra M. (ACS Omega, 2019)
This study presents a first report on ruthenium-catalyzed asymmetric transfer hydrogenation (ATH) of levulinic acid (LA) to chiral gamma-valerolactone (GVL). ATH of LA has been explored with Noyori's chiral catalyst (Ru-TsDPEN) in methanol solvent. Efficacy of ATH reaction of LA was investigated under different reactions conditions such as temperature, catalyst, and hydrogen donor concentration. The effect of various organic tertiary bases along with formic acid (FA) as a hydrogen donor was studied, and N-methylpiperidine with FA (1:1 molar ratio) was revealed as an efficient hydrogen donor for ATH of LA to GVL furnishing chiral GVL with complete conversion and 93% enantiomeric excess (ee). This operationally simple and mild ATH protocol was tested for practical applicability of ATH of LA obtained from biomass waste (rice husk and wheat straw) and furnished chiral GVL with 82% ee.

Perception of glycerol carbonate as green chemical: synthesis and applications - Gade, Swapna M.; Saptal, Vitthal B.; Bhanage, Bhalchandra M. (Catalysis Communications, 2022)
Glycerol carbonate (GC) is a prominent component in industrial practice and has a remarkable potential for the sophisticated applications. While GC has come into prominence due to the perceived overflow of glycerol (GLY) as a coproduct of biodiesel industry, its contemporary and future downstream applications are driving tremendous interest in recent years. This review comprises strategies for glycerol carbonate synthesis, properties and its applications. The conversion of GLY to GC via transesterification has appeared in consensus to be the most promising route. A detailed explanation of the effect of the catalysts and operating conditions on the GC yield to provide an updated understanding of the process are summarized. Future directions for GC production through catalytic transesterification are also discussed.
Keywords: Biodiesel; biofuels; catalysis; Glycerol; Glycerol carbonate; green chemistry; transesterification